2021
DOI: 10.17567/ataunidfd.757302
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Autoclave and Heat Polymerization Techniques of Internal Adaptation of Acrylic Resins

Abstract: Aim: Polymerization shrinkage of the resin and distortion of the denture base due to thermal stress is virtually unavoidable during the processing of dentuRes These adverse effects increase the gap between the denture base and underlying mucosa, resulting in an illfitting denture. A variety of methods have been used to evaluate the dimensional changes and/or adaptation accuracy of a denture base. This study compared the adaptation accuracy of maxillary complete denture bases processed using different polymeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Considering that monomer has a boiling point of 100.8 °C, during the conventional polymerization process, the monomer can evaporate and produce bubbles in the resin matrix, resulting in pore formation and deterioration in the PMMA mechanical characteristics. To avert this during autoclave polymerization, radical initiated polymerization is carried out, first at 60 °C to absorb all the free monomer, then at 100 °C or higher to crosslink the polymer [ 22 ]. Durkan et al [ 10 ] investigated the impact of autoclave polymerization on the transverse strength of PMMA in comparison to the conventional water bath method; their results showed that the transverse strength of specimens significantly increased with autoclave polymerization.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that monomer has a boiling point of 100.8 °C, during the conventional polymerization process, the monomer can evaporate and produce bubbles in the resin matrix, resulting in pore formation and deterioration in the PMMA mechanical characteristics. To avert this during autoclave polymerization, radical initiated polymerization is carried out, first at 60 °C to absorb all the free monomer, then at 100 °C or higher to crosslink the polymer [ 22 ]. Durkan et al [ 10 ] investigated the impact of autoclave polymerization on the transverse strength of PMMA in comparison to the conventional water bath method; their results showed that the transverse strength of specimens significantly increased with autoclave polymerization.…”
Section: Discussionmentioning
confidence: 99%